Thermoreversible carbamazepine in situ gel for intranasal delivery: development and in vitro, ex vivo evaluation - Mohananaidu, Keithanchali; Chatterjee, Bappaditya; Mohamed, Farahidah; Mahmood, Syed; Almurisi, Samah Hamed (Springer Nature, 2022)
Over the past decade, intranasal (IN) delivery has been gaining attention as an alternative approach to conventional drug delivery routes targeting the brain. Carbamazepine (CBZ) is available as an orally ingestible formulation. The present study aims to develop a thermoreversible in situ gelling system for delivering CBZ via IN route. A cold method of synthesis has been used to tailor and optimize the thermoreversible gel composition, using poloxamer 407 (P407) (15–20% w/v) and iota carrageenan (ɩ-Cg) (0.15–0.25% w/v). The developed in situ gel showed gelation temperatures (28–33°C), pH (4.5–6.5), rheological properties (pseudoplastic, shear thinning), and mucoadhesive strength (1755.78–2495.05 dyne/cm2). The in vitro release study has shown sustained release behavior (24 h) for gel, containing significant retardation of CBZ release. The release kinetics fit to the Korsmeyer–Peppas model, suggesting the non-Fickian diffusion type controlled release behavior. Ex vivo permeation through goat nasal mucosa showed sustained release from the gel containing 18% P407 with the highest cumulative drug permeated (243.94 µg/cm2) and a permeation flux of 10.16 µg/cm2/h. After treatment with CBZ in situ gel, the barrier function of nasal mucosa remained unaffected. Permeation through goat nasal mucosa using in situ gel has demonstrated a harmless nasal delivery, which can provide a new dimension to deliver CBZ directly to the brain bypassing the blood–brain barrier.